PERBEDAAN FERTILITAS ANTARA PENDUDUK PENDATANG DAN PENDUDUK LOKAL: SEBUAH STUDI KASUS DI DAERAH PERKOTAAN DI KOTA DENPASAR - Ida Putu Mudita (PIRAMIDA, 2009)
Discourse on migrants are frequent in Bali. In addition to several social effects, such as civilorder, crimes, slums, domintaion in informal sectors and so on, caused by them, discussions onmigrants also related to family planning program. There are opinions that point to migrants as thenon or less cooperative social groups to the program.This research asses the level of participation of migrants in family planning program in TegalKertha Village, West Denpasar, in Denpasar City. The topic brought up is the type of participationin family planning; the factors that have caused some migrant choose not to use contraception, andthe impact and meaning of their participation in family program.This research aim to determin the participation level of migrants in family planning program,factors causing unmet need and the impact and meaning of their participation. Its uses thecombination of both qualitative and quantitative methods. The data we used both primary andsecondary data. The theory applied in this research are The Theory of Participation, The Theory ofFeminism, and The Theory of Hegemony.There are six type of participation researched with the following result as follow: (1) first maritalage of migrant female is 20.6 years old, the highest is found on Batak ethnic group and the lowest isin Sasak ethnic group; (2) the average number of amount of person in a family in temporary residentis 3.1, while the number in permanent migrant is 4.3. The highest number is found in Java ethnicfamilies and the lowest is in Madura families; (4)the number of active FP participant for temporaryresident significantly lower compared to the those among permanent migrants; (5) the number oftemporary resident that uses long term contraception is only nine percent, rises to twenty twopercent among permanent migrant. The percentage of Bali is fourty three percent; (6) Thepercentage for male contraception among temporary resident is very low only one percent, but it ishiger among permanent migrants. The unmet need rate for temporary resident is at a very highnineteen percent and decreased to eight percent among permanent migrants.